Business Development Strategy Analysis of Taman Wisata Lebah - Abel - Gandhy (Program MM Universitas Surabaya, 2021)
Taman Wisata Lebah is an apiculture-based agritourism business own by PT Madu Pramuka. The emergence of competition and shift in business, demanding companies to develop and choose good business strategies, to ensure the companies survivability. Therefore, Taman Wisata Lebah need to conduct research concerning business development strategy, so that the business run by Taman Wisata Lebah, can develop in accordance with the times. The purposes of this research are to know the internal and external company factors, to know some alternative business strategies, also to know the priority alternative strategies to Taman Wisata Lebah. The research used IFE and EFE matrix to identify external and internal factors, the SWOT and IE matrix to formulate appropriate alternative strategies, QSPM matrix to determine the best alternative strategies priority. Based on the results of this research, the best alternative strategy to be applied is to develop Gerakan Pramuka-based activities for students in the Taman Wisata Lebah agritourism areas.